Kuznetz: A feasibility study of a sustainable kraft paper packaging venture in dynamic economy - Juan Miguel G. Aquitana, Jan Angelo M. Banzon, Erica Anne S. Lui, Micahella T. Padora, John Jemuel A. Panganiban, Bert P. Romero 4 0 16; 5
Abstract Plastic pollution has always been a pressing issue in the Philippines. A large percentage come from rivers in the Philippines. While the government has implemented various initiatives to reduce the usage of plastic, a minority of Filipinos tend to choose the traditional and cultural practice of Sachet economy. However, it is revealed from a survey that most majority of Filipino consumers tend to support enterprsies that innovate their materials and reduce plastic usage. Through this, there has been a rising awareness among Filipinos as some face the environment challenges and feel the brunt of it in the country. Kraft paper is a material that is eco-friendly as it is biodegradable and renewable. It is durable, adaptable, and brown-colored making it visually appealing as packaging, it encompasses various industries such as the food and beverage, retail, and e-commerce sectors. Its popularity has spread in various industries with the increasing need to be aware of and respond to environmental challenges. By relying on Kraft paper, it reduces dependence on plastic material. This is an opportunity for customers to transition towards an eco-friendly affordable packaging solution and meet the approval of its buyers as it combats plastic pollution. The firm aims to produce personalize packaging from sustainable materials like kraft paper. Companies can customize the packaging to meet their product and brand requirements. They can add unique designs, messages, and logos for marketing and brand distinction. This also allows businesses to conform to the consumer demand for sustainability and environmental laws. Kuznets aims to fulfill its obligations to conduct business sustainably, ethically, and responsibly whether it is for the consumers, its employees, and the stakeholders. The business is dedicated to doing its part for environmental preservation not just in its products as it is partnered with Fostering Education and Environment for Development Inc. (FEED). For its donations. The productions quality will always be high, and its standard will be vigorously monitored during its production and before it is packaged. Excess kraft paper will be surrendered to a junk shop as a recyclable material showing less waste produced in its production.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2